To find the discriminant of the quadratic equation, we need to rewrite it in the standard form: ax^2 + bx + c = 0.
The original equation is:
4x^2 - 45x - 269 = 7x^2 - 3x + 7
Rearranging terms:
7x^2 - 4x^2 - 45x + 3x - 269 - 7 = 0
Simplifying:
3x^2 - 42x - 276 = 0
Now we can identify the coefficients:
a = 3, b = -42, c = -276
The discriminant is calculated using the formula: D = b^2 - 4ac
Plugging in the values we have:
D = (-42)^2 - 4(3)(-276)
D = 1764 + 3312
D = 5076
Therefore, the discriminant of the equation is 5076.
For the following quadratic equation, find the discriminant.
4, x, squared, minus, 45, x, minus, 269, equals, 7, x, squared, minus, 3, x, plus, 7
4x
2
−45x−269=
7x
2
−3x+7
1 answer